THEORETICAL AND METHODOLOGICAL PROBLEMS OF USING DIGITAL EDUCATIONAL RESOURCES OF THE FUTURE TEACHER - Sydykhov Б.Д.; Kassiyetova А.Б.; Dikambay Н.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses some theoretical and methodological problems of using the digital educational resources of a future teacher. The study determines that the integrated use of the capabilities of information and telecommunication technologies in education can be achieved through the development and use of multifunctional digital educational resources that meet the current needs of the educational process, the features of the content, teaching methods and forms. The authors in the article, analyzing the scientific and pedagogical literature, the authors strive to show the direction of the introduction of digital educational resources in the educational process and the psychological principles of development necessary for their description and use, as well as the basic requirements of the educational system in digital educational resources.